2013
DOI: 10.1530/eje-13-0502
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for ‘asymptomatic’ mild primary hyperparathyroidism improves some clinical symptoms postoperatively

Abstract: Objective and background: Most primary hyperparathyroidism (pHPT) patients do not conform to the guidelines for parathyroidectomy established by an international panel of specialists and have a mild pHPT. This group is typically defined as 'asymptomatic'. The primary aim of this study was to determine symptom improvement in this 'asymptomatic' group after parathyroidectomy. Secondly, we aimed to create a preoperative clinical score predicting postoperative symptom resolution. Design: A prospective nonrandomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Interestingly, after surgery, the mild group had 9 of 10 domains on parity with the general population but the classic group had only 6, which once again suggests that PHPT disease severity may not predict symptom improvement with surgery and even those with ‘mild’ disease may experience symptom improvement. Blanchard et al reported that among asymptomatic patients with PHPT, which included some with normal calcium, nonspecific symptoms improved following parathyroidectomy . However, subgroup analyses showed greater symptom improvement, including depression, in those individuals with calcium above normal preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, after surgery, the mild group had 9 of 10 domains on parity with the general population but the classic group had only 6, which once again suggests that PHPT disease severity may not predict symptom improvement with surgery and even those with ‘mild’ disease may experience symptom improvement. Blanchard et al reported that among asymptomatic patients with PHPT, which included some with normal calcium, nonspecific symptoms improved following parathyroidectomy . However, subgroup analyses showed greater symptom improvement, including depression, in those individuals with calcium above normal preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐five non‐specific physical and neurocognitive symptoms described previously in association with mild PHPT were assessed using a self‐administered questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In two previous studies, Blanchard and colleagues evaluated non‐specific symptoms and their impact on QoL in patients with Hc‐m‐PHPT who were later treated by parathyroidectomy; they concluded that surgery does improve QoL and non‐specific symptoms in this group, with better results among younger patients. These findings form the basis of the present study of whether the same non‐specific symptoms are observed in NcPHPT, how these affect QoL, and whether parathyroidectomy could help alleviate some of these symptoms or improve the QoL of patients with normocalcaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Younger patients and those with higher preoperative calcium levels showed the best improvement [59].…”
Section: D2 Neuropsychological Symptomsmentioning
confidence: 93%
“…Younger patients and those with higher preoperative calcium levels (>10.4 mg/dL) show the best improvement [59]. However, it is important to consider that PTX, particularly if performed by unexperienced neck surgeons, may be complicated by side effects, which could be invalidating and not acceptable in a subject with a mild disease associated with a good quality of life.…”
Section: C Should Surgery Be Considered In All Patients?mentioning
confidence: 99%